THE EXISTENCE OF COVER FIDELITY INSURANCE IN THE DEVELOPMENT OF WAREHOUSE RECEIPT SYSTEM IN INDONESIA - Paramudhita, H. Radea Respati; Sinaga, H.Obsatar (CENTRAL ASIA AND THE CAUCASUS, 2022)
Warehouse Receipt System (WRS) is an activity related to the issuance, transfer, guarantee, and settlement of Warehouse Receipt transactions. The Warehouse Receipt System is one of the essential and effective instruments in the financing system. This is evidenced by credit facilities for farmers and the business world with collateral for goods stored in warehouses. The Warehouse Manager will then issue the goods stored in the Warehouse a Warehouse Receipt for the Goods Owner. Then the Warehouse Receipt is used as collateral/guarantee to the Financial Institution (Bank/Non-Bank) because the Warehouse Receipt is guaranteed with commodities always maintained and managed by an accredited Warehouse Manager (having a permit from Bappebti). As for ensuring that there is no loss for the parties, then in the provisions of the law in Indonesia, WRS must be equipped with insurance as a party that guarantees compensation for losses. Insurance in WRS certainly varies, but in this study, what the author will explore is fidelity insurance. Fidelity insurance itself is insurance against fraud or theft committed by the warehouse employee concerned. The study results indicate that fidelity insurance does not provide a guarantee to the parties involved in this case, the Property Owner as the Owner and the Financial Institution as the recipient of the guarantee who suffers losses due to an act of dishonesty/cheating committed by Warehouse Management employees. Still, this fidelity insurance becomes an obstacle in implementing WRS because fidelity insurance is one of the obstacles to the professionalism of Warehouse Managers in managing their warehouses. In addition, there are difficulties in proving the dishonesty/cheating act committed, then to what extent the insurance company covers the dishonesty/cheating of the Warehouse Manager employee.